International Interest Rates, Exchange Rates, and the Stochastic Structure of Supply - BOYLE, GLENN W. (Journal of Finance, 1990)
ABSTRACT In a dual‐currency, flexible exchange rate model, both nominal and real foreign exchange premia depend on investor risk attitudes, consumption parameters, and the stochastic structure of currency and commodity supplies. When supplies are random, their joint correlation structure determines the sign of the premia. If the money supplies are identically distributed, then all foreign exchange premia, regardless of the currency of denomination, are zero. A positive correlation between the value of a country's currency and its nominal interest rate need not indicate real interest rate movements. Relative bond prices can be negatively correlated with the terms of trade.